(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This article analyses the non-existent, probable or concrete relationships between both writers: Cervantes and Tirso de Molina. The analysis focuses on four aspects: the probability that both of them met and knew each other, the presence of Tirso in the works by Cervantes, the influence of Cervantes in the plays of Tirso and Cervantes evocation in the works of the friar.